Supervisory behaviour and employee work engagement: interpersonal and institutional trust as mediator - Ahamed, Forbis; Hassan, Arif (Inderscience Enterprises Ltd. , UK, 2014)
This paper examines the mediating role of interpersonal and organisational trust in the relationship of ransformational leadership style with employees’ work engagement. A sample of 395 bank employees rated their immediate supervisors’ leadership behaviour, interpersonal and organisational trust and work engagement. The results confirmed all the hypotheses.Transformational leadership was significantly associated with interpersonal and intuitional trust as well as work engagement. Both forms of trust also predicted work engagement. The test of mediation effect of trust in the relationship between transformational leadership style and employees work engagement indicated the full mediation effects of both forms of trust, i.e. interpersonal and institutional trust.